Construction and Engineering Application of an Anti-Disturbance Control Power Supply System for Key Auxiliary Equipment in Coal-Fired Power Plants Under Weak Grid Conditions - Zhao Hancheng (Asian Journal of Social and Humanities, 2026)
In response to the frequent occurrence of grid disturbances such as voltage sags caused by the weak grid structure in the area where the Datang Jinguang Kalteng Power Plant in Indonesia is located, which have led to power-loss trips of key auxiliary equipment including the coal feeder control system and motor-operated valves (MOVs), posing a serious threat to the safe and stable operation of the generating units, this study carries out applied research and engineering retrofitting of an anti-grid-disturbance control power supply system. Through systematic analysis of historical grid disturbance characteristics and the tolerance capabilities of coal feeder control equipment, a high-reliability control power upgrade solution based on online double-conversion UPS and an intelligent power distribution system is designed and implemented, establishing a "secure power supply zone" effectively isolated from grid disturbances. The project completed system design, equipment selection, engineering implementation, and commissioning verification on schedule. Operational results demonstrate that the new system significantly improves the power supply reliability of the coal feeder system under grid disturbance conditions, providing a replicable and scalable technical approach for ensuring reliable power supply to key auxiliary equipment in coal-fired power plants located in weak grid regions.